2021
DOI: 10.1186/s12951-021-00789-5
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional lipid-based nanocarriers with antibacterial and anti‐inflammatory activities for treating MRSA bacteremia in mice

Abstract: Background Bacteremia-induced sepsis is a leading cause of mortality in intensive care units. To control a bacterial infection, an immune response is required, but this response might contribute to organ failure. Kidneys are one of the main organs affected by bacteremia. Combination therapies with antibacterial and anti-inflammatory effects may be beneficial in treating bacteremia. This study aimed to develop nanostructured lipid carriers (NLCs) loaded with ciprofloxacin and rolipram that exert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Similarly, Li et al (2020) showed that in an in vitro cytotoxicity experiments revealed that FTP NPs were less toxic to mammalian cells than PMET, and in vivo intravenous injection of FTP NPs revealed no acute toxicity. In another study reported by Liao et al (2021), it was found that treatment with nanostructured lipid carriers (NLCs) encapsulating both ciprofloxacin and rolipram significantly reduced MRSA count in mice liver and kidneys compared with the free drugs. In addition, Mekkawy et al (2017) observed much higher antibacterial activity, as well as wound healing promotion of Na CMC hydrogel loaded with PEG-coated AgNPs as compared to silver sulfadiazine cream using MRSA-infected wound mice model.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Li et al (2020) showed that in an in vitro cytotoxicity experiments revealed that FTP NPs were less toxic to mammalian cells than PMET, and in vivo intravenous injection of FTP NPs revealed no acute toxicity. In another study reported by Liao et al (2021), it was found that treatment with nanostructured lipid carriers (NLCs) encapsulating both ciprofloxacin and rolipram significantly reduced MRSA count in mice liver and kidneys compared with the free drugs. In addition, Mekkawy et al (2017) observed much higher antibacterial activity, as well as wound healing promotion of Na CMC hydrogel loaded with PEG-coated AgNPs as compared to silver sulfadiazine cream using MRSA-infected wound mice model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nanocarriers decrease the apparent volume distribution, in turn allowing maximum tolerated dose and causing bacterial cell death at much lower antibiotic concentrations and thus expanding the spectrum of action against MDR bacteria. Various biopolymers including proteins, carbohydrates and lipids have been used to synthesize nanocarriers with promising antibacterial activities [144]. For example, linalool-functionalized hollow mesoporous silica spheres efficiently improved the bactericidal activities of the organic component against both Gram-negative (E. coli) and Gram-positive (S. aureus) bacteria by breaking the cell membrane structure [145].…”
Section: Antibiotic Nanocarriersmentioning
confidence: 99%
“…Coating the NP surface with a biocompatible polymer (e.g., polyethylene glycol (PEG)) prolongs the blood circulation time by preventing opsonization and reducing absorption by the reticuloendothelial system. For example, rifamipicin (RIF) in a mannose and PEG-coated graphene oxide NC is increasingly endocytosed into macrophages via the mannose receptor, thereby increasing the concentration of RIF in macrophages infected with M. tuberculosis [ 97 ], encapsulated VAN into the pillar [ 5 ] arenes covered with mannose are taken up by MRSA-infected macrophages, in which VAN is subsequently released due to the acidic pH and the presence of cathepsin B [ 98 ] or NLCs containing ciprofloxacin (CIP) and rolipram coated with retinol to ensure active transport of NLCs via retinol-binding protein 4 to the kidney for the treatment of bacteremia [ 99 ]. Dicloxacillin-loaded and CS-coated liposomes have been proven to be a promising NC with increased antibiotic delivery to MRSA [ 100 ].…”
Section: Nanosystems and Their Benefitsmentioning
confidence: 99%